Anthrax in the Russian Federation: Improvement of Epizootic-Epidemiological Surveillance at the Present Stage - E. G. Simonova; S. A. Kartavyaya; S. R. Raichich; M. N. Loktionova; A. A. Shabeykin (Эпидемиология и вакцинопрофилактика)
The improvement of epizootic-epidemiological surveillance of anthrax in the Russian Federation acquires particular urgency in modern conditions. The aim of the study was to assess the current  situation of anthrax in the Russian Federation and to develop and implement effective technologies of epizootic-epidemiological  surveillance. The materials of the study were data from official  statistics, information-analytical and archival materials; GIS  «Anthrax» data and The Cadastre of the settlements characterized  by persistent risk of anthrax in the Russian Federation, as well as  materials of publications and results of own researches. The modern  manifestations of both epizootic and epidemic processes of anthrax  in the Russian Federation, characterized by the occurrence of  outbreaks during the reduce in incidence of anthrax among humans  and animals, were revealed. The directions of the current  surveillance system have been determined.